Confidence and Intentions to Help a Person at Risk of Suicide. Issue 1 (24th July 2019) - Nicholas, Angela; Pirkis, Jane; Rossetto, Alyssia; Jorm, Anthony; Spittal, Matthew; Reavley, Nicola
Abstract : Objective: We aimed to identify Australian adults' current level of confidence and intentions to help a person close to them in distress or at risk of suicide to inform the content and targeting of suicide prevention messages aimed at family and friends of those at risk. Methods: We conducted a nationally representative computer‐assisted telephone survey of confidence and intentions to help someone in distress or at risk of suicide ( n  = 3, 002). We used logistic regression to determine whether sociodemographic and exposure variables predicted confidence and intentions to help. Results: Confidence to help was high. About half of the respondents had intentions inconsistent with best practice. Listening and talking, and encouraging the person to seek professional help were the most common types of intended helping actions. Intentions to ask suicide risk assessment questions were least common. Men were more likely than women to have intentions to carry out nonrecommended actions, and less likely to have intentions to carry out recommended actions. Conclusions: Suicide prevention messaging aimed at family and friends could encourage them to ask direct questions about suicide risk and could include messages about "what not to do." Suicide prevention messages aimed specifically at men are indicated.